2011
DOI: 10.1021/bi101605p
|View full text |Cite
|
Sign up to set email alerts
|

Low-Spin Heme b3 in the Catalytic Center of Nitric Oxide Reductase from Pseudomonas nautica

Abstract: Respiratory nitric oxide reductase (NOR) was purified from membrane extract of Pseudomonas (Ps.) nautica cells to homogeneity as judged by polyacrylamide gel electrophoresis. The purified protein is a heterodimer with subunits of molecular masses of 54 and 18 kDa. The gene encoding both subunits was cloned and sequenced. The amino acid sequence shows strong homology with enzymes of the cNOR class. Iron/heme determinations show that one heme c is present in the small subunit (NORC) and that approximately two he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 63 publications
6
66
0
1
Order By: Relevance
“…Therefore, assays were performed at 42°C, which is below the optimum growth temperature. The turnover number (k cat ) obtained at 42°C for the TtcNOR is considerably smaller than those reported for other cNORs (5,6,13,16,18,20). The highest activity obtained with the TtcNOR was about 9 electrons (e − )/min (at 42°C) with the electron donor PMS (phenazine methosulfate) ( Table 1), which presumably donates electrons directly to the active site in the NorB subunit without involving the heme c in the NorC subunit (5).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, assays were performed at 42°C, which is below the optimum growth temperature. The turnover number (k cat ) obtained at 42°C for the TtcNOR is considerably smaller than those reported for other cNORs (5,6,13,16,18,20). The highest activity obtained with the TtcNOR was about 9 electrons (e − )/min (at 42°C) with the electron donor PMS (phenazine methosulfate) ( Table 1), which presumably donates electrons directly to the active site in the NorB subunit without involving the heme c in the NorC subunit (5).…”
mentioning
confidence: 82%
“…Enzymes belonging to the cNOR family have been isolated from five denitrifying bacteria: Pseudomonas stutzeri (12, 13), Paracoccus denitrificans (14,15), Halomonas halodenitrificans (16,17), Roseobacter denitrificans (18,19), Pseudomonas nautica (20), and Pseudomonas aeruginosa, for which an X-ray structure has been reported (5,21). All of these strains are in the Proteobacteria phylum.…”
mentioning
confidence: 99%
“…NORs have been isolated from different denitrifying organisms, such as Paracoccus denitrificans [1,2], and several Pseudomonas species, such as stutzeri [3,4], aeruginosa [5] and nautica [6], currently known as Marinobacter hydrocarbonoclasticus [7]. This enzyme belongs to the bacterial denitrification pathway (NO 3 − → NO 2 − → NO → N 2 O → N 2 ), where NO 3 − is the electron acceptor, being reduced to N 2 in consecutive redox reactions, mediated by different metalloenzymes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There are three proposed mechanisms on the basis of the structural, spectroscopic, and theoretical studies (26)(27)(28)(29). Using a rapid freeze quench method combined with electron paramagnetic resonance spectroscopy, we found that simultaneous formation of ferrous heme-NO and ferrous Fe B -NO at 0.5 ms after the introduction of NO into fully reduced cNOR (26).…”
Section: Tablementioning
confidence: 99%
“…In cis-heme b 3 mechanism, first NO molecule coordinates to heme b 3 , followed by the cis-hyponitrite formation upon the direct binding of second NO to heme-bound NO. There is also alternative suggestion of cis-Fe B mechanism in which two NO molecules bind to nonheme Fe B (29), because ferrous heme-NO species would be highly stable dead end product.…”
Section: Tablementioning
confidence: 99%